2005
DOI: 10.1039/b503906a
|View full text |Cite
|
Sign up to set email alerts
|

Co-transport of H+/Cl– by a synthetic prodigiosin mimic

Abstract: An amidopyrrole with appended imidazole group can bind and co-transport H+/Cl- across vesicle membranes much more effectively than an analogue with an appended pyridyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 25 publications
(10 reference statements)
2
70
0
1
Order By: Relevance
“…The data in Figure 4 shows that the background proton efflux rate is quite substantial due to the large pH gradient. This feature has been observed previously and is discussed in reference 4 . Hydrogen bonded dimer of the HCl complex of 3 with selected atom labelling.…”
Section: Acknowledgmentssupporting
confidence: 69%
See 2 more Smart Citations
“…The data in Figure 4 shows that the background proton efflux rate is quite substantial due to the large pH gradient. This feature has been observed previously and is discussed in reference 4 . Hydrogen bonded dimer of the HCl complex of 3 with selected atom labelling.…”
Section: Acknowledgmentssupporting
confidence: 69%
“…3 Recently, we demonstrated that compound 2 is a weak chloride receptor at neutral pH but when protonated shows a significantly enhanced chloride binding affinity. 4 Transport studies showed that 2 functions as an HCl co-transporter in vesicles, and that transport was accelerated by the presence of a pH gradient. More recently, J.T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Despite the obvious importance of transmembrane bicarbonate transport, there have been no reports, to the best of our knowledge, of "small" molecules that are capable of promoting bicarbonate transport across lipid membranes, in contradistinction to the growing body of work on chloride and HCl transport across phospholipid vesicle membranes. [9][10][11][12][13][14][15] Phospholipid vesicles have been extensively investigated because of their usefulness as models for biological membranes. Unilamellar vesicles of a specific size are easily produced with control of the entrapped solution.…”
mentioning
confidence: 99%
“…This family of natural products exhibits promising anticancer, antimicrobial and immunosuppressive activities. [2][3][4][5] Published work, [2,[6][7][8][9] including some from commercial ventures, demonstrates that interest in the anticancer activities of prodigiosin analogues is currently high. While biological studies on synthetic prodigiosin derivatives (prodigiosenes) [10] showed that the methoxy group in ring B is essential for anticancer activity, [11,12] fine tuning of the structure through derivatisation of the A and C rings is somewhat tolerated.…”
mentioning
confidence: 99%